Kinerja Program Studi Administrasi Pendidikan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta (Ditinjau dari Pelayanan dalam Bidang Kurikulum, Sistem Pembelajaran, dan Suasana Akademik) - Dewi Ariyani Wahyuningrum; Rugaiyah Rugaiyah; Desi Rahmawati (Program Studi Manajemen Pendidikan, 2017)
Research conducted at the Administration of Education Study Program Facultyof Education, State University of Jakarta. This reasearch aimed to describe theperformance of the study program in providing good educational services for students aslearners through curriculum applied by the program of study which includes theperformance of courses in the curriculum development system is supported by learningand academic atmosphere. This study is an evaluative method deskripstif conducted tosee the performance of Administration of Education Study Program Faculty of Education,State University of Jakarta using a qualitative and quantitative approach. Evaluationmodel used is the model Discrepancy Evaluation Model (DEM). The data obtained byresearchers is through observation, interviews, and documentation. Key informantinterviews were conducted to the Chairman of Study Program UNJ AP FIP, and issupported by a supporter informant consisting of lecturers, TU Staff, and Student StudyProgram UNJ AP FIP.The reasearch concluded that 1) the performance component of courses onaspects of curriculum development shows the categories very good, 2) the performancecomponent of courses there are aspects of the implementation of learning systems, fromfour (4) aspects of the implementation of the learning system there are two componentsindicate the category of very good: execution learning process, efforts to improve thelearning system. Components of the implementation of the guiding thesis showed goodcategory. While the implementation of the components of academic guidance indicatesless category. 3) the performance component of study program there is the aspect ofincreasing academic atmosphere, showing very good category. Based on the acquisitionof these three components, it can be said the performance of the study program ofEducational Administration Faculty of Education at the Jakarta State UniversityCurricula Aspects, Learning Systems and academic atmosphere showed very goodcategory.